Solution of 2D non-homogenous wave equation by using polywave functions - Sokała, Małgorzata (Computer Assisted Methods in Engineering and Science, 2009)
The paper presents a specific technique of solving the non-homogenous wave equation with the use of Trefftz functions for the wave equation. The solution was presented as a sum of a general integral and a particular integral. The general integral was expressed in the form of a linear combination of Trefftz functions for the wave equation. In order to obtain the particular integral polywave functions were used. They were generated by using the inverse operator L-1 of the equation taking into consideration the Trefftz functions.